Towards a circular building industry through digitalisation: Exploring how digital technologies can help narrow, slow, close, and regenerate the loops in social housing practice - Çetin, Sultan (A+BE | Architecture and the Built Environment, 2023)
This thesis explores the integration of Circular Economy (CE) principles of narrow, slow, close, and regenerate in the social housing practice through digital technologies. Beginning with the examination of the CE implementation in Dutch social housing organisations, the research extends its focus to the broader built environment, introducing the Circular Digital Built Environment Framework and identifying ten enabling technologies. Subsequent chapters explore realworld applications of these digital technologies in circular new built, renovation, maintenance, and demolition projects of forerunner social housing organisations. The thesis includes a comprehensive study of material passports, addressing challenges around data management and proposing a digitally-enabled framework. The thesis concludes with critical reflections on the findings and their implications and provides further recommendations for research and practical applications in advancing circularity in the building industry through digital technologies.